Paleodrainage and fault development in the southern Perth Basin, Western Australia during and after the breakup of Gondwana from 3D modelling of the Bunbury Basalt - Olierook, H.; Timms, Nicholas Eric; Merle, Renaud; Jourdan, F.; Wilkes, P. (Taylor and Francis Ltd., 2015)
The evolution of faults and paleodrainage patterns on the southwestern Australian passive margin during and after the breakup of Gondwana in the Early Cretaceous remains poorly understood. This contribution investigates the fault and paleodrainage evolution in the southern Perth Basin with the use of the ‘Bunbury Basalt’, the only lava flows known to be synchronous with continental breakup. New aeromagnetic data have been integrated with well intersections and outcrop constraints to establish the first 3D model of the Bunbury Basalt. The model reveals that flows are up to 100 m thick and are predominantly confined to two north–south-trending paleovalleys and their tributaries situated in the Bunbury Trough in the southern Perth Basin. The Donnybrook Paleovalley flow ponded in a paleovalley proximal to the Darling Fault and is truncated by the two later flows within the Bunbury Paleovalley, which is positioned centrally in the Bunbury Trough. Offsets of the Bunbury Basalt have been used to identify new northeast- and northwest-trending faults in the southern Perth Basin, and broad folding is interpreted as a consequence of drag into the Darling and Busselton faults. The model has been used to determine post-basalt net displacements for the Darling and Busselton faults of 370 and 210 m, respectively, and <175 m for the northeast and northwest-trending faults. The source vents for the Bunbury Basalt were probably located at extensional jogs at intersections between the Darling Fault and subordinate oblique faults. These results challenge the views on longstanding quiescence of the post-breakup western Australian passive margin.